The epidemiology of out-of-hospital cardiac arrest in Australia and New Zealand: A binational report from the Australasian Resuscitation Outcomes Consortium (Aus-ROC). (March 2022) - Bray, Janet; Howell, Stuart; Ball, Stephen; Doan, Tan; Bosley, Emma; Smith, Karen; Dicker, Bridget; Faddy, Steven; Thorrowgood, Melanie; Swain, Andy; Thomas, Andrew; Wilson, Alexander; et al.
Abstract: Introduction: The Australasian Resuscitation Outcomes Consortium (Aus-ROC) out-of-hospital cardiac arrest (OHCA) Epistry (Epidemiological Registry) now covers 100% of Australia and New Zealand (NZ). This study reports and compares the Utstein demographics, arrest characteristics and outcomes of OHCA patients across our region. Methods: We included all OHCA cases throughout 2019 as submitted to the Epistry by the eight Australian and two NZ emergency medical services (EMS). We calculated crude and age-standardised incidence rates and performed a national and EMS regional comparison. Results: We obtained data for 31, 778 OHCA cases for 2019: 26, 637 in Australia and 5, 141 in NZ. Crude incidence was 107.9 per 100, 000 person-years in Australia and 103.2/100, 000 in NZ. Overall, the majority of OHCAs occurred in adults (96%), males (66%), private residences (76%), were unwitnessed (63%), of presumed medical aetiology (83%), and had an initial monitored rhythm of asystole (64%). In non-EMS-witnessed cases, 38% received bystander CPR and 2% received public defibrillation. Wide variation was seen between EMS regions for all OHCA demographics, arrest characteristics and outcomes. In patients who received an EMS-attempted resuscitation (13, 664/31, 778): 28% (range across EMS = 13.1% to 36.7%) had return of spontaneous circulation (ROSC) at hospital arrival and 13% (range across EMS = 9.9% to 20.7%) survived to hospital discharge/30-days. Survival in the Utstein comparator group (bystander-witnessed in shockable rhythm) varied across the EMS regions between 27.4% to 42.0%. Conclusion: OHCA across Australia and NZ has varied incidence, characteristics and survival. Understanding the variation in survival and modifiable predictors is key to informing strategies to improve outcomes.